Looking Back at Big Data. - Hoffmann, Leah (Communications of the ACM, 2013)
The author discusses the use of Big Data in history research, and mentions the relationship between historians and computer scientists in terms of digital historical archives, digital publishing, and online research resources. Computational history research conducted by Adam Jatowt from the University of Kyoto is discussed, as well as collective memory, data mining, and probability distributions. A study on fame conducted by Internet company Google is mentioned, as well as journalism trends research, the British Old Bailey Online law archive, and historian William Turkel.